Large-scale separation of silybin diastereoisomers using lipases - Gažák, R. (Radek); Marhol, P. (Petr); Purchartová, K. (Kateřina); Monti, D.; Biedermann, D. (David); Riva, S.; Cvak, L.; Křen, V. (Vladimír) (Process Biochemistry, 2010)
The flavonolignan silybin (1), isolated from the seeds of milk thistle (Silybum marianum), occurs in nature as an equimolar mixture of two diastereoisomers, silybin A and silybin B, that exhibit different biological activities. The preparative production of optically pure silybin A and B in a diastereoisomeric purity greater than 95 percent was accomplished using immobilized Candida antarctica lipase B (Novozym 435) in a combination of two reactions: regioselective acetylation of a natural silybin mixture (1) and subsequent stereoselective alcoholysis of the resulting 23-O-acetylsilybin (2). Several grams of the optically pure substances can be produced within one week using this new, robust and scalable process, which is selective, mild and high-yielding